2015
DOI: 10.3390/rs71013664
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Variation in Ice-Cover Characteristics of the Slave River, Canada Using RADARSAT-2 Data—A Case Study

Abstract: Abstract:The winter regime of river-ice covers in high northern latitude regions is often a determining factor in the management of water resources, conservation of aquatic ecosystems and preservation of traditional and cultural lifestyles of local peoples. As ground-based monitoring of river-ice regimes in high northern latitudes is expensive and restricted to a few locations due to limited accessibility to most places along rivers from shorelines, remote sensing techniques are a suitable approach for monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Monitoring of the course and structure of ice phenomena on rivers makes it easier to forecast climate changes, and allows us to determine whether any given climatic tendency is permanent [34][35][36][37]. The ice cover occurs less frequently than the remaining phases of the icing cycle, while factors conducive to its formation are frosty winters and the longer-term persistence of negative air temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of the course and structure of ice phenomena on rivers makes it easier to forecast climate changes, and allows us to determine whether any given climatic tendency is permanent [34][35][36][37]. The ice cover occurs less frequently than the remaining phases of the icing cycle, while factors conducive to its formation are frosty winters and the longer-term persistence of negative air temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted on river ice analysis with SAR data has taken several directions: study of the values of backscatter coefficients for different types of ice cover (Gherboudj, Bernier, & Leconte, 2010); automatic algorithms for ice types classification (Chu, Das, & Lindenschmidt, 2015;Chu & Lindenschmidt, 2016;Gauthier, Tremblay, Bernier, & Furgal, 2010;Mermoz, Allain, Bernier, Pottier, & Gherboudj, 2009); study of ice thickness (Kämäri, Alho, Colpaert, & Lotsari, 2017;Mermoz et al, 2014). However, few studies are found that examine how SAR data parametersfrequency, polarization and incidence angleinfluence the possibility of detecting specific ice types.…”
Section: Introductionmentioning
confidence: 99%
“…RIVICE can also simulate the flow dynamics for an ice-covered river by increasing the wetted perimeter to include the width of the underside of the cover. For a solid ice cover, the roughness coefficient now becomes a composite value nc of both the bed and ice roughness coefficients, nb and ni respectively: (2) nb is assumed constant for all in-stream hydraulic conditions of a river reach. For ice covers formed by ice rubble or slush the roughness n can be set as a function of ice thickness h through a relationship established by Nezhikhovskiy [30]:…”
Section: River Hydraulic and Ice Processes Modelled In Rivicementioning
confidence: 99%
“…Rubble or slush ice also has the potential to jam and dam up a river section, causing even more backwater staging and river banks and levees to overflow and flood the surrounding floodplain. From an ecological perspective, many floodplain and wetland ecosystems require such periodic flooding for their replenishment of moisture, sediment and nutrients, especially in perched ponds and lakes of inland deltas such as, for example in Canada, the Peace-Athabasca Delta in Alberta [1], the Slave River Delta in the Northwest Territories [2,3] and the Saskatchewan River Delta along the Saskatchewan/Manitoba boundary [4,5]. However, ice jams and the flooding they induce can pose threats to, and wreak damage on, many communities located along these rivers.…”
Section: Introductionmentioning
confidence: 99%